Anti-lightning aluminum electrolytic capacitor and manufacturing method thereof

By using high-purity aluminum foil, pressurized into aluminum foil, optimized electrolytic paper and electrolyte solution in aluminum electrolytic capacitors, combined with lightning strike additives and special sealing technology, the problem of insufficient lightning strike resistance of existing aluminum electrolytic capacitors has been solved, and the further development has been achieved. High lightning resistance and longer service life.

CN119446792APending Publication Date: 2025-02-14SHENZHEN XINZHONGYUAN ELECTRONICS CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411584084.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing aluminum electrolytic capacitors have shortcomings in their lightning resistance performance, which is difficult to withstand high lightning voltage, which can easily lead to damage to the capacitor and affect the normal operation of electronic equipment.

Method used

High-purity aluminum foil and 18-30μm thick pressurized aluminum foil as electrodes are used, combined with electrolytic paper with high insulation strength, low dielectric loss and electrolyte solution with high flash fire voltage, low viscosity and high stability, and lightning-resistant additives are added. And through special sealing technology and aging treatment, the lightning resistance of the capacitor is improved.

Benefits of technology

It significantly improves the lightning resistance performance of aluminum electrolytic capacitors, can effectively resist the high voltage and high current shocks caused by lightning strikes, extends the service life of the capacitor, and reduces equipment maintenance costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to the technical field of aluminum electrolytic capacitor manufacturing, in particular to an anti-lightning aluminum electrolytic capacitor and a manufacturing method thereof.The anti-lightning aluminum electrolytic capacitor comprises an anode foil, a cathode foil, electrolytic paper, electrolyte, a rubber plug, a guide pin and an aluminum shell, the guide pin is riveted to the surfaces of the anode foil and the cathode foil, and the anode foil and the cathode foil are isolated through the electrolytic paper; and winding to form a capacitor core package, infiltrating the core package by the electrolyte, filling the core package into an aluminum shell, sealing the aluminum shell by a rubber plug to form an aluminum electrolytic capacitor, and aging the capacitor to obtain a finished product. According to the anti-lightning aluminum electrolytic capacitor and the manufacturing method thereof provided by the invention, the high-conductivity covering film and the optimized positive foil structure are adopted, so that the anti-lightning aluminum electrolytic capacitor has relatively high compression strength and anti-lightning capability, stable performance can be kept when the anti-lightning aluminum electrolytic capacitor is subjected to strong current impact such as lightning stroke, and the reliability and the safety of electronic equipment are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of aluminum electrolytic capacitor manufacturing, and in particular to a lightning-resistant aluminum electrolytic capacitor and a manufacturing method thereof. Background Art

[0002] As we all know, aluminum electrolytic capacitors, as an important electronic component, are widely used in various electronic devices, including but not limited to power supplies, communication equipment, computer motherboards, automotive electronic systems, etc. It plays a key role in energy storage, filtering, coupling, decoupling, etc. in the circuit. For example, in the power supply, aluminum electrolytic capacitors can smooth the DC output voltage, reduce voltage ripple, and ensure stable power supply for subsequent circuits; in audio equipment, it can effectively filter out clutter in audio signals and improve sound quality. Its unique large capacity characteristics make it irreplaceable in many electronic circuits; with the widespread use of modern electronic devices, they face more and more threats from the external environment, among which lightning strikes are a very destructive factor. The instantaneous high voltage and high current pulses generated by lightning can invade electronic devices through power lines, signal lines or direct inductive coupling. When lightning strikes the power line, it may generate a surge voltage of up to tens of thousands of volts or even higher, which far exceeds the normal operating voltage range of electronic equipment. For aluminum electrolytic capacitors, such high voltage may cause breakdown of its internal dielectric and damage to its electrodes. In outdoor electronic equipment such as communication base stations, the probability of lightning strikes is relatively high. Once struck by lightning, the damage to the aluminum electrolytic capacitors may further cause failures in the entire communication system, resulting in communication interruption, which brings great inconvenience to people's lives and work. In the design and manufacturing process of aluminum electrolytic capacitors on the market, most of them do not fully consider the lightning resistance performance. The problems of the existing technology are: in the use of electronic equipment, instantaneous high voltage shocks such as lightning strikes are common problems, which may cause serious damage to electronic components. Traditional aluminum electrolytic capacitors have insufficient lightning resistance performance and are difficult to withstand high lightning voltages, which can easily cause capacitor damage and affect the normal operation of electronic equipment; In summary, in view of the key role of aluminum electrolytic capacitors in electronic equipment and the serious harm caused by lightning strikes, and considering the shortcomings of existing aluminum electrolytic capacitors in lightning resistance, there is an urgent need to develop an aluminum electrolytic capacitor with good lightning resistance and a manufacturing method thereof. Summary of the invention

[0003] 1. Technical problems solved In view of the deficiencies in the prior art, the present invention provides a lightning-resistant aluminum electrolytic capacitor and a manufacturing method thereof, which has the advantage of excellent lightning-resistant performance.

[0004] (II) Technical solution The above technical objectives of the present invention are achieved through the following technical solutions: an aluminum electrolytic capacitor resistant to lightning strikes, comprising an anode foil, a cathode foil, electrolytic paper, an electrolyte, a rubber plug, a guide pin and an aluminum shell, wherein the guide pin is riveted to the surface of the anode foil and the cathode foil, the anode foil and the cathode foil are separated by the electrolytic paper, and are wound to form a capacitor core package, the electrolyte infiltrates the core package, and the aluminum shell is filled and sealed by the rubber plug to form an aluminum electrolytic capacitor, and the capacitor is subjected to aging treatment to obtain a finished product; The anode foil is made of high-purity aluminum foil and is subjected to special surface treatment to increase its compressive strength and specific capacity. The cathode foil is made of 18-30 μm thick, pressurized aluminum foil.

[0005] Electrolytic paper is made of materials with high insulation strength and low dielectric loss, and is processed through a dry paper composite process to improve its voltage resistance and maintain its liquid absorption capacity.

[0006] The electrolyte is an organic solvent with high conductivity and good stability to ensure the stable performance of the capacitor during long-term use. The aluminum shell is designed to have good heat dissipation performance to prevent the heat generated when high current passes through from causing overheating of the capacitor. In addition, a layer of insulating paint is coated on the surface of the aluminum shell to enhance its corrosion resistance and extend the service life of the capacitor. In the production process of the capacitor, special attention is also paid to the cleanliness and dryness of each component to avoid the influence of impurities and moisture on the performance of the capacitor. Through these technical measures, the aluminum electrolytic capacitor of the present invention has been significantly improved in lightning resistance and can effectively resist the high voltage and high current impact caused by lightning.

[0007] The electrolyte adopts an electrolyte solution with high flash voltage, low viscosity and high stability, and adds specific anti-lightning additives to improve the capacitor's tolerance to instantaneous high voltage shocks.

[0008] During the packaging process of the capacitor, a special sealing technology is used to ensure that the electrolyte will not leak due to temperature changes or long-term use. This sealing technology not only improves the reliability of the capacitor, but also extends its service life. In addition, the lead of the capacitor uses high-purity copper wire and is specially treated to reduce resistance, thereby reducing the heat loss of the capacitor during operation. The casing of the capacitor is designed to have good mechanical strength and can withstand a certain degree of physical shock and vibration, ensuring stable operation even in harsh environments. Through these comprehensive technical improvements, the aluminum electrolytic capacitor of the present invention has been significantly improved in lightning resistance and can effectively resist the high voltage and high current shocks caused by lightning strikes.

[0009] The present invention is further provided as follows: a method for manufacturing an aluminum electrolytic capacitor resistant to lightning strikes, wherein the anode foil is prepared by selecting a high-purity aluminum foil as the anode foil material, and undergoing cleaning, corrosion, and chemical processing to form an oxide film on the surface of the aluminum foil to improve its compressive strength.

[0010] The present invention is further configured as follows: the preparation of the cathode foil: selecting a material with good electrical conductivity, and subjecting the high-purity aluminum foil to cleaning, annealing and low-pressure chemical treatment to improve its surface flatness and specific volume.

[0011] The present invention is further configured as follows: the processing of the electrolytic paper: selecting electrolytic paper materials with high insulation strength and low dielectric loss, and using ultra-high voltage-resistant electrolytic paper using a dry paper composite process to improve the insulation properties between the positive and negative electrodes of the capacitor.

[0012] The present invention is further configured as follows: the preparation of the electrolyte: selecting an electrolyte solution with high flash voltage, low viscosity and high stability, and adding a specific anti-lightning additive, which is easy to penetrate the core package and improves the capacitor's tolerance to strong electrical shocks from lightning strikes.

[0013] The present invention is further configured as follows: the preparation formula of the lightning strike resistant electrolyte includes the following: a solvent, a solute and an additive; The solvent is: ethylene glycol: accounting for 40%-60% of the total mass. It has good solubility and stability and can provide a suitable ion transmission environment; Propylene glycol: 20%-40% of the total mass. Used in combination with ethylene glycol, it can adjust the viscosity and boiling point of the electrolyte; The solute is: boric acid: accounting for 5%-15% of the total mass. It plays the role of providing ions, adjusting pH value and enhancing stability in the electrolyte; Ammonium phosphate: 3%-10% of the total mass. It helps to improve the conductivity and lightning resistance of the electrolyte. The additives are: Lightning resistance additive A: 1%-5% of the total mass. The additives are: zinc oxide, titanium oxide, borated polyvinyl alcohol, boric acid ester, etc., which can enhance the capacitor's tolerance to strong lightning shocks; Hydrogen remover: 0.5%-2% of the total mass. Hydrogen remover is nitrobenzene compounds such as hydroquinone, p-nitrobenzyl alcohol, m-nitroacetophenone, o-nitrobenzene ether, etc., which prevents the internal pressure from rising and improves the stability and life of the capacitor; Defoamer: 0.1%-1% of the total mass. Reduce the foam generated during the preparation and use of the electrolyte.

[0014] The present invention is further configured as follows: the preparation step of the lightning strike resistant electrolyte comprises the following steps: firstly preparing raw materials, secondly dissolving solutes, then adding additives, then filtering and adjusting, and finally packaging and storing; S1: Prepare raw materials: accurately weigh ethylene glycol, propylene glycol, boric acid, ammonium phosphate, lightning protection additive A, dehydrogenation agent and defoaming agent according to the above formula. Ensure that the purity and quality of the raw materials meet the requirements; S2: Dissolve the solute: Slowly add the weighed boric acid and ammonium phosphate into the mixed solvent of ethylene glycol and propylene glycol, stirring while adding. A magnetic stirrer or a mechanical stirrer can be used, and the stirring speed is moderate to ensure that the solute is fully dissolved and avoid local overheating. The stirring time is 1-2 hours, until the solution becomes uniform and transparent; S3: Add additives: Add the anti-lightning additive A, dehydrogenating agent and defoaming agent to the dissolved solution in sequence. Continue stirring for a while to make the additives fully mixed. The stirring time is 0.5-1 hour; S4: Filtration and adjustment: Filter the prepared electrolyte through a filter to remove impurities and insolubles. You can use a microporous filter membrane or filter paper for filtration. If needed, you can adjust the performance of the electrolyte, such as adjusting the pH value and conductivity. This can be achieved by adding a small amount of acid-base regulator or adjusting the proportion of solutes; S5: Packaging and storage: Put the filtered electrolyte into a clean, sealed container to avoid contact with air, moisture and impurities. Glass bottles, plastic bottles or metal containers can be used for packaging. The container should have good sealing and corrosion resistance.

[0015] The present invention is further configured as follows: the storage temperature of the lightning protection electrolyte prepared in S5 is between 5-30°C.

[0016] The present invention is further configured as follows: the packaged capacitor is subjected to aging treatment, the aging voltage is optimized, and a segmented aging method is adopted, firstly aging is performed at a lower voltage for a period of time, and then the voltage is gradually increased until the set aging voltage is reached.

[0017] The purpose of aging treatment is to stabilize the performance of the capacitor and reduce its performance fluctuations during use. During the aging process, the chemical reaction inside the capacitor tends to be stable, and the passivation layer on the electrode surface is strengthened, thereby improving the reliability and life of the capacitor. The optimization of the aging voltage is determined experimentally, and it is necessary to take into account the material properties, design parameters and expected working environment of the capacitor. The segmented aging method can effectively avoid damage to the capacitor caused by applying too high a voltage at one time, and it can also shorten the overall aging time and improve production efficiency. After the aging is completed, the capacitor will undergo a series of performance tests to ensure that it meets the design specifications and application requirements.

[0018] The present invention is further configured as follows: the aluminum shell is 98.5% pure aluminum, the rubber plug is high temperature resistant peroxide-cured hydrogenated nitrile rubber, and during the production process of the lightning-resistant aluminum electrolytic capacitor, the burrs on the electrode edge are reduced through precise cutting process and surface treatment technology, thereby improving the lightning-resistant performance of the capacitor.

[0019] During the assembly process of the capacitor, automated equipment is used for precise assembly to ensure that the contact area between the electrode and the electrolyte is maximized while reducing the risk of internal short circuits. After assembly, the capacitor must undergo rigorous testing, including testing of parameters such as capacitance, loss factor, insulation resistance and leakage current to ensure that each capacitor meets the design requirements. In addition, the present invention also relates to a special packaging technology that can effectively prevent the expansion or contraction of the electrolyte due to temperature changes during long-term use, thereby extending the service life of the capacitor. Through these comprehensive measures, the lightning-resistant aluminum electrolytic capacitor finally prepared not only has excellent lightning-resistant performance, but also can maintain stable electrical performance in harsh environments such as high temperature and high humidity.

[0020] (III) Beneficial effects Compared with the prior art, the present invention provides a lightning-resistant aluminum electrolytic capacitor and a manufacturing method thereof, which has the following beneficial effects: The lightning-resistant aluminum electrolytic capacitor and the manufacturing method thereof have high compressive strength and lightning resistance by adopting a high-conductivity coating and an optimized positive foil structure, can maintain stable performance when subjected to strong electrical shocks such as lightning strikes, and improve the reliability and safety of electronic equipment. The burrs are reduced by a precise cutting and manufacturing process, the internal structure of the capacitor is optimized, and the reliability and stability of the capacitor are improved. The burrs are reduced by a precise cutting and manufacturing process, the internal structure of the capacitor is optimized, and the reliability and stability of the capacitor are improved.

[0021] The lightning-resistant aluminum electrolytic capacitor and its manufacturing method. By optimizing the material and manufacturing process, while resisting lightning damage, it also reduces the impact of other electrical stresses on the capacitor in daily work. This improvement in comprehensive performance slows down the aging rate of the capacitor and extends its service life. Compared with traditional capacitors, under the same use environment (including an environment that may be struck by lightning), the capacitor of the present invention can maintain good electrical performance for a longer period of time, reduce the frequency of replacing capacitors, and reduce equipment maintenance costs and environmental impact. DETAILED DESCRIPTION

[0022] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0023] A lightning-resistant aluminum electrolytic capacitor and a manufacturing method thereof, comprising an anode foil, a cathode foil, electrolytic paper, an electrolyte, a rubber plug, a guide pin and an aluminum shell. The preparation of the anode foil: a high-purity aluminum foil is selected as the anode foil material, and after cleaning, corrosion and chemical processing, an oxide film is formed on the surface of the aluminum foil to improve its pressure resistance. The preparation of the cathode foil: a material with good conductive properties is selected, and the high-purity aluminum foil is subjected to cleaning, annealing and low-pressure chemical processing to improve its surface flatness and specific capacitance. The processing of the electrolytic paper: an electrolytic paper material with high insulation strength and low dielectric loss is selected. , using ultra-high voltage-resistant electrolytic paper made by dry paper composite process to improve the insulation properties between the positive and negative electrodes of the capacitor, the preparation of the electrolyte: select an electrolyte solution with high flash voltage, low viscosity and high stability, and add specific anti-lightning additives to easily penetrate the core package, while improving the capacitor's tolerance to strong electric shocks from lightning strikes, the guide pins are riveted to the surface of the anode foil and the cathode foil, the anode foil and the cathode foil are isolated by electrolytic paper, and are wound to form a capacitor core package. Before winding, the prepared electrodes and dielectric layers are inspected to ensure that there are no damage, impurities and other problems on the surface.The electrodes and dielectric layers are placed at the corresponding positions of the winding machine. The tension control system of the winding machine is set to a tension between 5-7N and a winding speed of 200mm / s. During the winding process, the alignment accuracy of the electrodes and dielectric layers is ensured to be within ±0.1mm by the laser alignment system to ensure the tightness and uniformity of the winding. After the winding is completed, the capacitor core is formed, and the dimensions of the core are measured (length, diameter, etc.) to ensure that it meets the design specifications. The electrolyte infiltrates the core package, which is then sealed by a rubber plug after being loaded into an aluminum shell to form an aluminum electrolytic capacitor. The dielectric constant is selected. The insulating sealant with a dielectric strength of 3.5 and a dielectric strength of 20kV / mm is used to place the capacitor core into a polycarbonate shell mold. The insulating sealant is injected into the shell by an automatic glue injection device. The injection amount is 80% of the shell volume. During the glue injection process, the pressure of the glue injection device is controlled at [0.1-0.8]MPa to ensure that the glue can evenly fill the internal space of the shell. After the insulating sealant is injected, the capacitor is left to stand at 25°C for 24 hours to allow the sealant to fully cure. The hardness of the cured sealant is measured by a hardness tester. The hardness value is required to be between The Shore A hardness is between 40 and 100 to ensure good sealing and protection effects. The capacitor is aged to obtain the finished product. The anode foil is made of high-purity aluminum foil and undergoes special surface treatment to increase its compressive strength and specific capacitance. The cathode foil is 18 to 30 μm thick and pressurized aluminum foil. The electrolytic paper is made of materials with high insulation strength and low dielectric loss, and is processed by dry paper composite process to improve its voltage resistance and maintain liquid absorption capacity. The electrolyte uses an electrolyte solution with high flash voltage, low viscosity and high stability, and adds specific anti- Lightning additives improve the capacitor's ability to withstand instantaneous high-voltage shocks. The packaged capacitors are aged and the aging voltage is optimized. A segmented aging method is used to first age the capacitors at a lower voltage for a period of time, and then gradually increase the voltage until the set aging voltage is reached. The aluminum shell is 98.5% pure aluminum, and the rubber plug is high-temperature resistant peroxide-cured hydrogenated nitrile rubber. In the production process of lightning-resistant aluminum electrolytic capacitors, precise cutting technology and surface treatment technology are used to reduce the burrs on the electrode edges and improve the capacitor's lightning resistance.

[0024] Wherein: the preparation formula of the lightning protection electrolyte includes the following: solvent, solute and additive; The solvent is: Ethylene glycol: 40%-60% of the total mass. It has good solubility and stability and can provide a suitable ion transmission environment; Propylene glycol: 20%-40% of the total mass. Used in combination with ethylene glycol, it can adjust the viscosity and boiling point of the electrolyte; The solute is: boric acid: 5%-15% of the total mass. It provides ions, adjusts pH value and enhances stability in the electrolyte; Ammonium phosphate: 3%-10% of the total mass. Additives that help improve the conductivity and lightning resistance of the electrolyte are: Lightning resistance additive A: 1%-5% of the total mass, borated polyvinyl alcohol, boric acid ester, etc., can enhance the capacitor's tolerance to strong lightning shocks; Hydrogen remover: 0.5%-2% of the total mass. Hydrogen remover is nitrobenzene compounds such as hydroquinone, p-nitrobenzyl alcohol, m-nitroacetophenone, o-nitrobenzene ether, etc., which prevents the internal pressure from rising and improves the stability and life of the capacitor; Defoamer: 0.1%-1% of the total mass. Reduce the foam generated during the preparation and use of the electrolyte.

[0025] The preparation steps of the lightning strike resistant electrolyte are as follows: first, prepare the raw materials, accurately weigh ethylene glycol, propylene glycol, boric acid, ammonium phosphate, lightning strike resistant additive A, dehydrogenation agent and defoamer according to the above formula. Ensure that the purity and quality of the raw materials meet the requirements, then dissolve the solute, slowly add the weighed boric acid and ammonium phosphate to the mixed solvent of ethylene glycol and propylene glycol, and stir while adding. A magnetic stirrer or a mechanical stirrer can be used, and the stirring speed is moderate to ensure that the solute is fully dissolved and avoid local overheating. The stirring time is 1-2 hours until the solution becomes uniform and transparent, and then the additives are added, and the lightning strike resistant additive A, dehydrogenation agent and defoamer are added to the dissolved solution in sequence. Continue stirring for a period of time to fully mix the additives, and the stirring time is 0.5-1 hour, followed by filtering and adjusting, filtering the prepared electrolyte through a filter to remove impurities and insolubles therein, and a microporous filter membrane or filter paper can be used for filtering. The performance of the electrolyte can be adjusted as needed, such as adjusting the pH value and conductivity. This can be achieved by adding a small amount of acid-base regulator or adjusting the ratio of solutes. Finally, package and store the filtered electrolyte into a clean, sealed container to avoid contact with air, moisture and impurities. Glass bottles, plastic bottles or metal containers can be used for packaging. The container should have good sealing and corrosion resistance. The storage temperature of the prepared lightning-resistant electrolyte is between 5-30°C.

[0026] Data comparison table of traditional capacitors and this lightning protection capacitor: Capacitor parameters Traditional capacitors Lightning protection capacitor Rated capacitance(μF) 100 100 Withstand voltage(V) 500 600 Lightning protection voltage(KV) 2 6.6 Equivalent series resistance (mΩ) 10 8 Loss tangent 0.1 0.08 (I) Lightning resistance voltage test A lightning simulated voltage impact test was performed on the aluminum electrolytic capacitor of the present embodiment. A lightning surge generator was used. The test parameters were set according to international standards (such as IEC 61000-4-5), and the surge voltage amplitude was gradually increased. The test results showed that the capacitor of the present invention can withstand a surge voltage of up to 6.6KV, while the traditional aluminum electrolytic capacitor of the same specification had a dielectric breakdown phenomenon when the surge voltage reached 2KV.

[0027] During the test, the performance of the capacitor was stable, without any signs of performance degradation or damage. In addition, through comparative tests, the equivalent series resistance and loss tangent of the lightning protection capacitor were better than those of traditional capacitors, indicating that it is more efficient and has less energy loss in high-frequency applications. The test results further verified the reliability and superiority of the lightning protection capacitor under extreme voltage conditions, providing a safer and more stable power supply solution for electronic equipment.

[0028] The steps of preparing the dielectric layer in this embodiment are: 1-preparation of composite dielectric material, 2-coating of dielectric layer. 1- Preparation steps of composite dielectric materials: 1-1 Preparation and mixing of raw materials: Prepare barium titanate ceramic powder and polyimide as the main components of the composite dielectric material. The average particle size of the barium titanate ceramic powder is 1 μm, and the particle size is measured and screened by a laser particle size analyzer to ensure that the particle size meets the requirements. Polyimide is selected from products with a specific molecular weight ([specific molecular weight value]) to ensure its performance.

[0029] Barium titanate ceramic powder and polyimide are mixed in a high-speed mixer in a mass ratio of 3:2. The stirring speed of the high-speed mixer is set to 1000 r / min and the stirring time is 3 hours. During the stirring process, N-methylpyrrolidone is gradually added as a dispersant. The mass ratio of the added amount of N-methylpyrrolidone to the composite medium material is 1:2, so that the materials are mixed more evenly to form a paste-like composite medium material.

[0030] The viscosity of the paste composite medium material is measured using a rotational viscometer, and the viscosity value is required to reach [specific viscosity value] mPa·s to ensure good coating performance. At the same time, the mixed material is analyzed by a Fourier transform infrared spectrometer (FT-IR) to confirm the chemical bonding of the material and ensure that the material performance meets the design requirements.

[0031] 2-Dielectric layer coating steps: 2-1 Coating equipment and parameter settings: Use precision coating equipment to coat the dielectric layer. Before coating, control the working environment temperature of the coating equipment at 25°C and the humidity at 50% to ensure the stability of the coating quality. Set the coating speed to 5mm / s. According to the designed thickness of the dielectric layer (total thickness 25μm), coating is performed three times, and the coating thickness is controlled at 8-9μm each time.

[0032] After each coating, the electrode with the coating layer is dried in a drying oven at 80°C for 2 hours. During the drying process, the thickness change of the dielectric layer is monitored in real time by an optical microscope to ensure that the thickness error is controlled within ±1μm. After completing three coatings, the dielectric layer is fully inspected again using an optical microscope to observe its surface flatness and the presence of defects such as cracks and holes. At the same time, the dielectric constant of the dielectric layer is measured using a dielectric constant tester to ensure that it meets the design requirements (the dielectric constant is between [specific range]).

[0033] (II) Lightning current test (pulse width 8 / 20μs) A lightning surge generator is used to inject simulated lightning current pulses into the capacitor, with a pulse width of 8 / 20μs (8μs leading edge, 20μs half-peak time). When the peak current of the capacitor in this embodiment reaches 500A, the electrodes and lead wires are well connected, and the temperature rise of the capacitor shell does not exceed 30°C (ambient temperature is 25°C). In contrast, when the peak current of the traditional aluminum electrolytic capacitor reaches 100A, the connection between the electrode and the lead wire becomes obviously loose, the temperature rises sharply to more than 80°C, and local damage occurs inside the capacitor, resulting in a capacitance value change of more than 10% (normal capacitance value change should be less than 5%).

[0034] (III) Stability test in the power circuit of communication base stations (6 months, covering the lightning season, 10 lightning events) The lightning-resistant aluminum electrolytic capacitor of the present invention was applied to the power supply circuit of a communication base station for an actual operation test of 6 months (covering the lightning season). During the test period, a total of 10 lightning strikes were monitored, and various parameters of the power supply circuit were measured after each lightning strike. The results show that the ripple factor of the power supply voltage is always kept within ±3% (normal operation requires a ripple factor of less than ±5%), and the equivalent series resistance (ESR) of the capacitor changes by no more than 20% (the initial ESR value is [specific value] mΩ). In the comparison communication base station using traditional capacitors, there were 3 power failures after the lightning strike, resulting in communication interruption. The power supply voltage ripple factor increased to more than ±10% after the lightning strike, and the ESR of the traditional capacitor increased by more than 50%, requiring the capacitor to be replaced and repaired to resume normal operation.

[0035] In this embodiment, the electrode preparation is an aluminum foil pretreatment step - a nickel plating process step - a conductive polymer coating coating step, wherein: 1. The aluminum foil pretreatment step includes raw material selection and inspection, a cleaning process and an etching process 1-1 Raw material selection and inspection: First, high-purity aluminum foil (purity 99.99%) is selected as the basic material for the electrode. Each batch of aluminum foil is strictly inspected for quality, including thickness measurement (using a high-precision thickness gauge with a measurement accuracy of ±0.1μm), surface flatness inspection (detecting surface roughness through an optical interferometer with a Ra value of less than 0.2μm) and impurity content analysis (using spectral analysis technology to ensure that the impurity content is within the specified range). Only aluminum foil that meets the quality standards is used for subsequent production.

[0036] The initial size of the aluminum foil is determined according to the capacitor design specifications. For example, for a capacitor with a capacity of 100 μF and a rated voltage of 450 V, the length of the aluminum foil is selected to be 500 mm, the width is 300 mm, and the thickness is 100 μm.

[0037] 1-2 Cleaning process: The selected aluminum foil was placed in an ultrasonic cleaning device, and acetone was used as the cleaning solvent. The frequency of the ultrasonic cleaning device was set to 40kHz, the power was 200W, and the cleaning time was 10 minutes. During this process, the acetone solvent can effectively dissolve impurities such as oil and dust on the surface of the aluminum foil. After cleaning, the aluminum foil was rinsed with deionized water to remove the residual acetone, and then dried in a vacuum drying oven at 60°C for 30 minutes to ensure that the surface of the aluminum foil was completely dry.

[0038] 1-3 Etching treatment: Prepare an acidic etching solution, using a phosphoric acid-sulfuric acid mixture, in which the phosphoric acid concentration is 30% (mass fraction) and the sulfuric acid concentration is 10% (mass fraction). Put the cleaned aluminum foil into the etching solution, and the etching process is carried out in an etching tank with temperature control and stirring functions. The etching temperature is precisely controlled at 60°C, the stirring speed is 100r / min, and the etching time is 5 minutes. The microscopic surface structure of the etched aluminum foil is observed by scanning electron microscopy (SEM) to ensure that the surface area is increased by about 30% to increase the capacitance value. The etched aluminum foil is rinsed again with deionized water and dried in hot air at 80°C for 15 minutes.

[0039] Among them, 2. The nickel plating process steps are: equipment preparation and parameter setting and nickel plating process monitoring 2-1 Equipment preparation and parameter setting: Use vacuum sputtering equipment for nickel plating. Before nickel plating, evacuate the vacuum sputtering equipment to a high vacuum degree of 1×10-3Pa to ensure the purity of the nickel plating environment. Introduce argon gas into the equipment as sputtering gas, and the argon gas flow rate is controlled at 50sccm (standard cubic centimeters per minute).

[0040] The sputtering power was set to 200 W, the sputtering time was set to 15 minutes, and the sputtering target material was a nickel target with a purity of 99.9%, a diameter of 300 mm, and a thickness of 5 mm.

[0041] 2-2 Nickel plating process monitoring: During the nickel plating process, the thickness of the nickel layer is monitored in real time by an optical thickness monitor. When the thickness of the nickel layer reaches the design requirement of 5μm, sputtering is stopped. After the nickel plating is completed, the nickel layer is microstructured using an electron microscope to observe the grain size (required to be between 10-20nm) and uniformity of the nickel layer. At the same time, a four-probe resistance tester is used to measure the resistivity of the nickel layer to ensure that it meets the conductivity requirements (resistivity is less than [specific value] Ω·cm).

[0042] 3. The steps of coating the conductive polymer coating are: coating preparation and coating and drying 3-1 coating preparation: The anti-oxidation conductive polymer coating was prepared, the solid content of the coating was 20% (mass fraction), and the solvent was toluene. During the preparation process, a high-precision electronic balance was used to weigh each component to ensure the accurate proportion. The coating was stirred in a high-speed stirrer at a speed of 1000r / min for 30 minutes to make the coating mixed evenly.

[0043] Use a filter with a pore size of 0.2μm to filter the paint to remove possible particulate impurities in it, ensure the purity of the paint, and avoid affecting the coating quality during the coating process.

[0044] After filtering, the coating is transferred to the coating equipment. The coating process uses a spin coating technique to ensure that the coating is uniform and free of bubbles. After coating, the aluminum foil is placed in an oven and dried at 120°C for 30 minutes to remove the solvent and cure the coating. After drying, the coating thickness is measured to ensure its uniformity and meet the design requirements. Finally, microstructural analysis is performed to verify whether the grain size and uniformity of the coating meet the expected standards.

[0045] 3-2 Coating and drying: The nickel-plated aluminum foil is immersed in the coating solution for 30 minutes. The immersion process is carried out in a constant temperature environment, and the temperature is controlled at 25°C to ensure the uniformity of the coating. After the immersion is completed, the aluminum foil is slowly removed from the coating solution using the pulling method, and the pulling speed is 5mm / s, so that a uniform coating layer is formed on the surface of the aluminum foil.

[0046] The coated aluminum foil was placed in a drying oven and dried at 60°C for 4 hours. During the drying process, the air in the drying oven circulated well to ensure that the solvent toluene could fully evaporate. The sheet resistance of the dried conductive polymer coating was measured by a surface resistance tester, which was required to be less than 10Ω / □. At the same time, an adhesion tester was used to check the adhesion between the coating and the nickel layer to ensure that the coating would not fall off during subsequent processing and use.

[0047] After the dried aluminum foil is cooled, the thickness of the nickel-plated layer is measured to ensure that its uniformity meets the technical requirements. Then, the surface of the aluminum foil is cleaned to remove any dust and residues that may exist. Finally, the aluminum foil is cut into the required size for subsequent capacitor assembly. The entire process strictly follows quality control standards to ensure that each step meets the predetermined technical indicators, thereby ensuring the performance and reliability of the final product.

[0048] During the cutting process, high-precision cutting equipment is used to ensure the accuracy of the aluminum foil size and the flatness of the edges. The cut aluminum foil will undergo a strict visual inspection to eliminate any possible defects or damage. Through these meticulous steps, the electrode material of the aluminum electrolytic capacitor is ensured to have superior electrochemical performance. After completing these steps, the aluminum foil will be sent to the capacitor assembly area and assembled into the final capacitor product together with the electrolyte and other components.

[0049] During the cutting process, precision cutting equipment is used to ensure the dimensional accuracy and smooth edges of the aluminum foil to avoid unnecessary stress or damage during capacitor assembly. The cut aluminum foil will be thoroughly cleaned to remove tiny metal chips or other impurities that may be generated during the cutting process. After cleaning, the aluminum foil is transferred to the dust-free workshop for capacitor assembly. During the assembly process, the aluminum foil is used as an electrode and rolled together with electrolytes, diaphragms and other materials to form the internal structure of the capacitor. After assembly, the capacitor unit will undergo an aging test to ensure its electrical performance is stable. After the aging test, the capacitor unit undergoes a final appearance inspection and electrical performance test, and qualified products will be marked, packaged, and ready to be shipped to customers.

[0050] This specific embodiment is only an explanation of the present invention, and it is not a limitation of the present invention. After reading this specification, those skilled in the art can make non-creative modifications to the present embodiment as needed. Although the embodiments of the present invention have been shown and described, it is understandable to those of ordinary skill in the art that various changes, modifications, substitutions and variations can be made to these embodiments without departing from the principle and spirit of the present invention. The scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A lightning-resistant aluminum electrolytic capacitor, comprising an anode foil, a cathode foil, electrolytic paper, an electrolyte, a rubber plug, a guide pin and an aluminum shell, characterized in that: The guide pins are riveted to the surfaces of the anode foil and the cathode foil, the anode foil and the cathode foil are separated by electrolytic paper, and are wound to form a capacitor core package, the electrolyte infiltrates the core package, and the core package is sealed by a rubber plug after being placed in an aluminum shell, thereby forming an aluminum electrolytic capacitor, and the capacitor is subjected to aging treatment to obtain a finished product; The anode foil is made of high-purity aluminum foil and has undergone special surface treatment to increase its compressive strength and specific capacity. The cathode foil is made of 18~30μm thick, pressurized aluminum foil. Electrolytic paper is made of materials with high insulation strength and low dielectric loss, and is processed by dry paper composite process to improve its voltage resistance and maintain liquid absorption capacity; The electrolyte adopts an electrolyte solution with high flash voltage, low viscosity and high stability, and adds specific anti-lightning additives to improve the capacitor's tolerance to instantaneous high voltage shocks.

2. The method for manufacturing a lightning-resistant aluminum electrolytic capacitor according to claim 1, characterized in that: Preparation of the anode foil: high-purity aluminum foil is selected as the anode foil material, and after cleaning, corrosion and chemical processing, an oxide film is formed on the surface of the aluminum foil to improve its compressive strength.

3. The method for manufacturing a lightning-resistant aluminum electrolytic capacitor according to claim 1, characterized in that: Preparation of the cathode foil: Select a material with good conductivity, and the high-purity aluminum foil is cleaned, annealed and treated with low-pressure chemical treatment to improve its surface flatness and specific capacity.

4. The method for manufacturing a lightning-resistant aluminum electrolytic capacitor according to claim 1, characterized in that: The electrolytic paper is processed by selecting electrolytic paper materials with high insulation strength and low dielectric loss, and using ultra-high voltage-resistant electrolytic paper produced by dry paper composite technology to improve the insulation properties between the positive and negative electrodes of the capacitor.

5. The method for manufacturing a lightning-resistant aluminum electrolytic capacitor according to claim 1, characterized in that: Preparation of the electrolyte: an electrolyte solution with high flash voltage, low viscosity and high stability is selected, and a specific anti-lightning additive is added to facilitate penetration of the core package, while improving the tolerance of the capacitor under strong electric shock from lightning.

6. The method for manufacturing a lightning-resistant aluminum electrolytic capacitor according to claim 5, characterized in that: The preparation formula of the lightning strike resistant electrolyte includes the following: a solvent, a solute and an additive; The solvent is: ethylene glycol: accounting for 40%-60% of the total mass. It has good solubility and stability and can provide a suitable ion transmission environment; Propylene glycol: 20%-40% of the total mass. Used in combination with ethylene glycol, it can adjust the viscosity and boiling point of the electrolyte; The solute is: boric acid: accounting for 5%-15% of the total mass. It plays the role of providing ions, adjusting pH value and enhancing stability in the electrolyte; Ammonium phosphate: 3%-10% of the total mass. Helps improve the conductivity and lightning resistance of the electrolyte The additives are: anti-lightning additive A: accounting for 1%-5% of the total mass, borated polyvinyl alcohol, boric acid ester, etc., which can enhance the capacitor's tolerance to strong electrical shocks from lightning strikes; Hydrogen remover: 0.5%-2% of the total mass. Hydrogen remover is nitrobenzene compounds such as hydroquinone, p-nitrobenzyl alcohol, m-nitroacetophenone, o-nitrobenzene ether, etc., which prevents the internal pressure from rising and improves the stability and life of the capacitor; Defoamer: 0.1%-1% of the total mass. Reduces the foam generated during the preparation and use of the electrolyte.

7. The method for manufacturing a lightning-resistant aluminum electrolytic capacitor according to claim 5, characterized in that: The preparation steps of the lightning strike resistant electrolyte include the following steps: firstly preparing raw materials, secondly dissolving solutes, then adding additives, then filtering and adjusting, and finally packaging and storing; S1: Prepare raw materials: accurately weigh ethylene glycol, propylene glycol, boric acid, ammonium phosphate, lightning protection additive A, dehydrogenation agent and defoaming agent according to the above formula. Ensure that the purity and quality of the raw materials meet the requirements; S2: Dissolve the solute: slowly add the weighed boric acid and ammonium phosphate into the mixed solvent of ethylene glycol and propylene glycol, stirring while adding. You can use a magnetic stirrer or a mechanical stirrer, stirring at a moderate speed to ensure that the solute is fully dissolved and avoid local overheating. The stirring time is 1-2 hours, until the solution becomes uniform and transparent; S3: Add additives: Add the anti-lightning additive A, dehydrogenating agent and defoaming agent to the dissolved solution in sequence. Continue stirring for a while to make the additives fully mixed. The stirring time is 0.5-1 hour; S4: Filtration and adjustment: Filter the prepared electrolyte through a filter to remove impurities and insolubles. You can use a microporous filter membrane or filter paper for filtration. If needed, you can adjust the performance of the electrolyte, such as adjusting the pH value and conductivity. This can be achieved by adding a small amount of acid-base regulator or adjusting the proportion of solutes; S5: Packaging and storage: Put the filtered electrolyte into a clean, sealed container to avoid contact with air, moisture and impurities. Glass bottles, plastic bottles or metal containers can be used for packaging. The container should have good sealing and corrosion resistance.

8. The method for manufacturing a lightning-resistant aluminum electrolytic capacitor according to claim 7, characterized in that: The storage temperature of the lightning protection electrolyte prepared in S5 is between 5°C and 30°C.

9. The lightning-resistant aluminum electrolytic capacitor according to claim 1, characterized in that: The packaged capacitor is subjected to aging treatment, the aging voltage is optimized, and a segmented aging method is adopted, firstly aging is performed at a lower voltage for a period of time, and then the voltage is gradually increased until the set aging voltage is reached.

10. The lightning-resistant aluminum electrolytic capacitor according to claim 1, characterized in that: The aluminum shell is made of 98.5% pure aluminum, the rubber plug is high temperature resistant peroxide-cured hydrogenated nitrile rubber, and during the production process of the lightning-resistant aluminum electrolytic capacitor, the burrs on the electrode edge are reduced through precise cutting process and surface treatment technology, thereby improving the lightning-resistant performance of the capacitor.

Citation Information

Cited By

  • Aluminum foil surface quality intelligent control method and system

    CN120954536A